Bakteri Aerob Penyebab Infeksi Nosokomial di Ruang Bedah RSU Abepura, Kota Jayapura, Papua - Daniel Lantang; Desi Paiman (Jurusan Biologi FMIPA Universitas Cenderawasih, 2012)
The research on identification of aerobic bacteria causing nosocomial infection in the surgery room of General Hospital (RSU) Abepura, Jayapura had been done from August–December 2008. Samples were taken from room air (30 minutes) using blood agar media and from certain tools at some points using brain heart infusion media (BHI). The colony appearance was observed after 24 hours of incubation period of bacterial growth. Further analysis to identify the aerobic bacteria causing nosocomial infections was done by several tests in Jayapura Health Laboratory. The result showed that there were 15 aerobic bacteria consisted of: the coccid gram–positive bacteria: Staphylococus epidermidis, S. aureus, S. saprophyticus, Streptcoccus sp; the rod gram-positive bacteria: Listeria monocytogenes, Diptheroid sp, Lactobacillus sp and gram-negative bacteria: Providence rettgeri, Pseudomonas puttrefaciens, Klebsiela ozaena, P. malthophyla, Morganela morganii, Serattia sp, K. oxytoca, and K. pneumonia. Key words: Aerobic bacteria, identification of bacteria, nosocomial infection, surgical room, Jayapura.